Cutaneous squamous cell carcinoma: state of the art, perspectives and unmet needs - Heppt, Markus; Leiter, Ulrike (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
Squamous cell carcinoma of the skin (cSCC) is one of the most common cancers of the Caucasian population and accounts for 20% of all cutaneous tumors. An S3 guideline from the German Guideline Program in Oncology has been available since 2019 and was updated in 2022. The diagnosis of cSCC is based on clinical examination. Excision and histological confirmation are required for clinically suspicious lesions to allow for prognostic assessment and correct treatment. The treatment of first choice is excision with complete histological assessment of the surgical margins. Adjuvant radiation therapy may be considered if there is a high risk of recurrence. The immune checkpoint inhibitor cemiplimab is approved and recommended as the treatment of first choice for locally advanced or metastatic cSCC in Europe. If contraindications are present, chemotherapy, EGFR inhibitors, or palliative radiation therapy may be used. Surveillance should be performed in a risk-stratified manner and includes a dermatological control supplemented by sonography examinations in high-risk patients. Much research is still needed for solid organ transplant patients, concomitant hematologic diseases, and cSCC showing primary or acquired resistance to immunotherapies. Current developments include new drug combinations, intralesional therapies alone or in combination with immune checkpoint inhibitors, and neoadjuvant approaches.
CRIS-Team Scopus Importer:2023-04-21
Keywords: cutaneous; immune checkpoint inhibitor; management; skin; squamous cell carcinoma; treatment